Improving the Creativity of Children with Disabilities Based on Local Culture: An Exploration of the “Karya.Ku” Program - Verisa, Grace Sava; Mutmainah, Nurul; Fidyastuti, Nita; Minsih, Minsih (IAS Journal of Localities, 2024)
The cultural activities based on “Karya.Ku” offer an innovative approach of improving the creativity of children with disabilities to be more positive and inclusive. This study aims to explore the various forms, factors, and implications of cultural activities based on “Karya.Ku” in facilitating self-expression, social interaction, as well as shaping people’s self-perception and views of children with disabilities. Descriptive qualitative methods were used to collect data through observations, interviews, and documentation of cultural activities based on “Karya.Ku” at the Alamanda special school for autism. The study involved principals, teachers, homeroom teachers, and students as informants. The findings of this study reveal that cultural activities based on “Karya.Ku” are significantly effective in enhancing the creativity of children with disabilities. This is achieved through the structured methodologies, the support for an inclusive learning environment, and the synergy between all parties. Furthermore, this study recommends the exploration of the implementation of cultural activities in other communities, with attention to the formation of attitudes.